Inovasi Sistem Informasi Manajemen sebagai Pendukung Pengambilan Keputusan di Lingkungan Pendidikan - Hendra Kurniawan; Saafira Najwaa An-Nada; Riska Khairani Siregar; Namirotul Arofat Lubis (Jurnal Manajemen Bisnis Digital Terkini, 2025)
The advancement of digital technology has driven the education sector to transform its information management and decision-making processes to become more effective. This study aims to examine the role of innovation in Management Information Systems (MIS) as a key support in the decision-making process within educational institutions. The research uses a qualitative descriptive approach, with data collection techniques including in-depth interviews, participatory observations, and documentation in several schools that have implemented MIS. Data analysis is conducted thematically to explore the effectiveness of MIS in supporting educational policy and operational management. The findings reveal that MIS has been implemented across various aspects of school management such as academic administration, finance, and reporting, significantly enhancing efficiency and transparency; it supports data-driven decision-making, enabling school principals and policymakers to make more accurate, measurable, and objective decisions; and although challenges such as limited digital infrastructure and human resource competencies exist, these can be addressed through training, mentoring, and the development of a technology-based work culture. Therefore, MIS proves to be an essential tool in establishing a modern, efficient, and sustainable education governance system.